PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS MULTIPLE REPRESENTASI PADA MATERI HUKUM DASAR KIMIA KELAS X IPA SMA NEGERI 1 SUNGAI RAYA - Abdullah Yamani Noor; Fitriani Fitriani; Dedeh Kurniasih (Universitas Muhammadiyah Pontianak, 2019)
This study was motivated by the learning sources used by students in Basic Laws of Chemistry that combines Concepts and Chemical Calculations completed by using Multiple Representations aspect. This study aimed to develop a valid, practical, and effective of student’s worksheet based on Multiple Representation for Basic Laws of Chemistry Class at the tenth Grade Natural Sciences of SMA Negeri 1 Sungai Raya. Using a Research and Development (R & D) of Borg and Gall model and One-shot case study design, the sample was selected by employing purposive sampling. The study indicated that student’s worksheet based on Multiple Representation was valid by 97,36% for material experts and 89,59% for media experts. Student’s worksheet was considered practical and received a positive response with an average practicality value of 95,58% for teacher responses and 88,64% for students responses. Additionally, student’s worksheet was effective, as the students successfully and classically completed the material by 79,68%. Therefore, student’s worksheet based on Multiple Representation is suitable as an alternative learning sources for the tenth grade Natural Sciences students.